Bimekizumab versus ustekinumab for the treatment of moderate to severe plaque psoriasis (BE VIVID): efficacy and safety from a 52-week, multicentre, double-blind, active comparator and placebo controlled phase 3 trial. Issue 10273 (6th February 2021) - Reich, Kristian; Papp, Kim A; Blauvelt, Andrew; Langley, Richard G; Armstrong, April; Warren, Richard B; Gordon, Kenneth B; Merola, Joseph F; Okubo, Yukari; Madden, Cynthia; Wang, Maggie; Cioffi, Christopher; et al.
Summary: Background: There is an unmet need for a treatment for psoriasis that results in complete skin clearance with a reliably quick response. Bimekizumab is a monoclonal IgG1 antibody that selectively inhibits interleukin (IL)-17F in addition to IL-17A. We aimed to compare the efficacy and safety of bimekizumab with placebo and ustekinumab in patients with moderate to severe plaque psoriasis over 52 weeks. Methods: BE VIVID was a multicentre, randomised, double-blind, active comparator and placebo controlled phase 3 trial done across 105 sites (clinics, hospitals, research units, and private practices) in 11 countries in Asia, Australia, Europe, and North America. Adults aged 18 years or older with moderate to severe plaque psoriasis (Psoriasis Area and Severity Index [PASI] score ≥12, ≥10% body surface area affected by psoriasis, and Investigator's Global Assessment [IGA] score ≥3 on a five point scale) were included. Randomisation was stratified by geographical region and previous exposure to biologics; patients, investigators, and sponsors were masked to treatment assignment. Patients were randomly assigned (4:2:1) using an interactive response technology to bimekizumab 320 mg every 4 weeks, ustekinumab 45 mg or 90 mg (baseline weight-dependent dosing) at weeks 0 and 4, then every 12 weeks, or placebo every 4 weeks. At week 16, patients receiving placebo switched to bimekizumab 320 mg every 4 weeks. All study treatments were administered as two subcutaneous injections. Coprimary endpoints were the proportion of patients with 90% improvement in the PASI (PASI90) and the proportion of patients with an IGA response of clear or almost clear (score 0 or 1) at week 16 (non-responder imputation). Efficacy analyses included the intention-to-treat population; safety analysis included patients who received at least one dose of study treatment. This trial was registered at ClinicalTrials.gov, NCT03370133 (completed). Findings: Between Dec 6, 2017, and Dec 13, 2019, 735 patients were screened and 567 were enrolled and randomly assigned (bimekizumab 320 mg every 4 weeks n=321, ustekinumab 45 mg or 90 mg every 12 weeks n=163, placebo n=83). At week 16, 273 (85%) of 321 patients in the bimekizumab group had PASI90 versus 81 (50%) of 163 in the ustekinumab group (risk difference 35 [95% CI 27–43]; p<0·0001) and four (5%) of 83 in the placebo group (risk difference 80 [74–86]; p<0·0001). At week 16, 270 (84%) patients in the bimekizumab group had an IGA response versus 87 (53%) in the ustekinumab group (risk difference 30 [95% CI 22–39]; p<0·0001) and four (5%) in the placebo group (risk difference 79 [73–85]; p<0·0001). Over 52 weeks, serious treatment-emergent adverse events were reported in 24 (6%) of 395 patients in the bimekizumab group (including those who switched from placebo at week 16) and 13 (8%) of 163 in the ustekinumab group. Interpretation: Bimekizumab was more efficacious than ustekinumab and placebo in the treatment of moderate to severe plaque psoriasis. The bimekizumab safety profile was consistent with that observed in previous studies. Funding: UCB Pharma.